Influenza Virus: A Master Tactician in Innate Immune Evasion and Novel Therapeutic Interventions - Hsu, Alan Chen-Yu (Frontiers in Immunology, 2018)
Influenza is a contagion that has plagued mankind for many decades, and continues to pose concerns every year, with millions of infections globally. The frequent mutations and recombination of the influenza A virus (IAV) cast a looming threat that antigenically novel strains/subtypes will rise with unpredictable pathogenicity and fear of it evolving into a pandemic strain. There have been four major influenza pandemics since the beginning of 20th century, with the great 1918 pandemic being the most severe, killing more than 50 million people worldwide. The mechanisms of IAV infection, host immune responses, and how viruses evade from such defensive responses at the molecular and structural levels have been greatly investigated in the last 30 years. While this has advanced our understanding of virus-host interactions and human immunology, and has led to the development of several antiviral drugs, they have minimal impact on the clinical outcomes of infection. The heavy use of these drugs has also imposed selective pressure on IAV to evolve and develop resistance. Vaccination remains the cornerstone of public health efforts to protect against influenza, however rapid mass-production of sufficient vaccines is unlikely to occur immediately after the beginning of a pandemic. This therefore requires novel therapeutic strategies against this continually emerging infectious virus, with higher specificity and cross-reactivity against multiple strains/subtypes of IAVs. This review discusses essential virulence factors of IAVs that determine sustainable human-to-human transmission, the mechanisms of viral hijacking of host cells and subversion of host innate immune responses, and novel therapeutic interventions that demonstrate promising antiviral properties against IAV. This hopefully will promote discussions and investigations on novel avenues of prevention and treatment strategies of influenza, that are effective and cross-protective against multiple strains/subtypes of IAV, in preparation for the advent of future IAVs and pandemics.